Impact of Energy Management Strategy Calibration on Component Degradation and Fuel Economy of Heavy-Duty Fuel Cell Vehicles. Issue 24 (2022) - Kölbl, Julian; Ferrara, Alessandro; Hametner, Christoph
Abstract: Energy management strategies significantly impact the fuel economy and component degradation of fuel cell electric vehicles by distributing the load demand between the battery and fuel cell systems. Since these are contrasting targets, designing a control strategy that finds a good trade-off is challenging. Therefore, this paper adopts a rule-based energy management strategy to show the significant impact of its calibration on fuel consumption and component degradation. The expected vehicle life is maximized by balancing battery and fuel cell degradation, assuming that individual component replacement is undesired. Moreover, the simulation results highlight the trade-off between fuel consumption and expected vehicle life, revealing that a slight increase in consumption can significantly mitigate the degradation. The study considers a sequence of six ld driving cycles for robust calibration of the energy management strategy. However, analyzing individual cycles reveals that even a robust calibration leads to significantly unbalanced degradation if the vehicle only runs a specific driving cycle. Therefore, this work proposes two potential research directions to cope with the mentioned issues and maintain the balance between fuel cell and battery degradation.